INTERPERSONAL METAFUNCTION IN PRESCHOOL ENROLLMENT BROCHURES: A SFL ANALYSIS IN LANGSA - Syafitri, Siska Eka; Purwati, Purwati (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study explores how interpersonal meaning is conveyed in preschool enrollment brochures through the lens of Systemic Functional Linguistics (SFL). Using a qualitative method to analyze 139 clauses, the research identifies a dominant use of statements (98.6%) over commands (2.2%), suggesting a preference for informative over directive communication. These results highlight the importance of interpersonal communication in promoting the school in order to make the parents read first, that is, the services provided by schools through various programs and their advantages. The language design is something important and interesting to discuss. The meaning conveyed by the presenter builds the interpersonal idea to be communicated. Brochures, as one of the visual media that consists of so many clauses, have their own way of sharing the information with the readers. The brochures of Pre-School Enrollment have their purpose of catching the parents' attention, making them intrigued to apply their children to the promoted schools. The researchers explore the written speech in the brochures by using the interpersonal metafunction of Systemic Functional Linguistics (SFL) by Halliday. The brochures were selected from some preschools in Langsa and ethical approval was also informed the days before to the institutions.